2015
DOI: 10.18632/oncotarget.5255
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and MDM2 single nucleotide polymorphisms influence survival in non-del(5q) myelodysplastic syndromes

Abstract: P53 is a key regulator of many cellular processes and is negatively regulated by the human homolog of murine double minute-2 (MDM2) E3 ubiquitin ligase. Single nucleotide polymorphisms (SNPs) of either gene alone, and in combination, are linked to cancer susceptibility, disease progression, and therapy response. We analyzed the interaction of TP53 R72P and MDM2 SNP309 SNPs in relationship to outcome in patients with myelodysplastic syndromes (MDS). Sanger sequencing was performed on DNA isolated from 208 MDS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The WT1 variant (rs16754) was described, by Damm et al, as a prognostic marker in AML patients that have normal cytogenetics, recognizing a favorable subgroup in the NPM1/FLT3 high‐risk group . Addicionally, McGraw et al reported the importance of TP53 and MDM2 gene variants in MDS prognosis and suggested that these variants provide a novel disease outcome scoring system independent of the IPSS . Likewise TP53 and MDM2 SNPs, the gene variants identified here may contribute to refine the current prognostic systems, namely through the better discrimination of MDS patients that have identical karyotypes by metaphase cytogenetics but different clinical phenotypes, and/or of AML patients that have normal cytogenetics.…”
Section: Discussionmentioning
confidence: 67%
“…The WT1 variant (rs16754) was described, by Damm et al, as a prognostic marker in AML patients that have normal cytogenetics, recognizing a favorable subgroup in the NPM1/FLT3 high‐risk group . Addicionally, McGraw et al reported the importance of TP53 and MDM2 gene variants in MDS prognosis and suggested that these variants provide a novel disease outcome scoring system independent of the IPSS . Likewise TP53 and MDM2 SNPs, the gene variants identified here may contribute to refine the current prognostic systems, namely through the better discrimination of MDS patients that have identical karyotypes by metaphase cytogenetics but different clinical phenotypes, and/or of AML patients that have normal cytogenetics.…”
Section: Discussionmentioning
confidence: 67%
“…Conversely, G-allele homozygosity was associated with inferior outcomes and terminal deletions involving 5q34 (P=0.05). In addition, McGraw et al (29) described the correlation of the TP53 single nucleotide polymorphism with survival in cases of non-del(5q) MDSs. Utilizing a novel functional SNP scoring system ranging from +2 to -2 based upon predicted p53 activity, the authors demonstrated the difference between the role of TP53 gene polymorphism R72P in del(5q) MDS patients and MDS patients with normal chromosome 5 (29).…”
Section: Asxl1 Tp53mentioning
confidence: 99%
“…16 Although TP53 mutation is observed in about 10% of all MDS patients, it is seen in 20% of del5q and in over 70% of complex karyotype patients, respectively. 13,17 However, increased expression of MDM2 is observed only in 10% of MDS patients. 17 The importance of p53 mutation in del5q subtype is related to RPS 14.…”
Section: Genetic and Epigenetic Abnormalitiesmentioning
confidence: 99%
“…13,17 However, increased expression of MDM2 is observed only in 10% of MDS patients. 17 The importance of p53 mutation in del5q subtype is related to RPS 14. This protein, which binds and inhibits MDM2, is subject to reduced expression in del5q.…”
Section: Genetic and Epigenetic Abnormalitiesmentioning
confidence: 99%